2014
DOI: 10.1039/c3ra44096f
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the interaction of cisplatin with β2-microglobulin: new insights into a chemotherapeutic drug

Abstract: Cisplatin is one of the most widely used anticancer platinum drugs and the interactions between cisplatin and proteins are deemed to be associated with its severe side-effects and drug resistance generated in the chemotherapy process. Here, the interaction of cisplatin with b2-microglobulin was investigated using electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI FTICR MS). High resolution MS data revealed that b2-microglobulin (b2M) can quickly react with cisplatin in 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…A study showed that within 24 h of intravenous injection, 65–98% of platinum is bound to proteins in the blood . There are considerable studies about the interactions of platinum metallodrugs with a variety of proteins such as human serum albumin (HSA), myoglobin, cytochrome c, ubiquitin, calmodulin, insulin, transferrin, lysozyme, copper‐containing proteins, beta 2‐microglobulin, and so on.…”
mentioning
confidence: 97%
“…A study showed that within 24 h of intravenous injection, 65–98% of platinum is bound to proteins in the blood . There are considerable studies about the interactions of platinum metallodrugs with a variety of proteins such as human serum albumin (HSA), myoglobin, cytochrome c, ubiquitin, calmodulin, insulin, transferrin, lysozyme, copper‐containing proteins, beta 2‐microglobulin, and so on.…”
mentioning
confidence: 97%